THE INFLUENCE OF BRAND TRUST IN MEDIATING CONSUMER ONLINE BEHAVIOR AGAINST BUYING INTEREST IN ONLINE STORES (CASE STUDY OF HYPERMART ONLINE SHOP IN INDONESIA) - Rahul Chauhan; Hendra Martha Fauzy (Dinasti International Journal of Digital Business Management, 2020)
The invasion of online stores in Indonesia is very massive, proven by various applications and online stores that are known to have operated and used services by the people in Indonesia. Changes in consumer shopping behavior from offline to online have become routine habits in daily behavior. This raises challenges for retail businesses in business continuity. To maintain business continuity, retail (offline store) must diversify by opening an online store. Having an online store or digital business format is expected to be able to maintain business continuity with the support of brand trust owned by offline stores.